Ground Water Investigation by Resistivity Method in the Drought Affected Area near Markundi District Mirzapur (U, P.) - Pandey, Sudhir Mohan (Annals of Arid Zone, 2016)
Reconnaissance investigations to locale suitable aquifers were carried out utilising electrical resistivity methods in Markundi area of Mirzapur district. Wenner's configuration, in particular, was made use of and Tagg's method of interpretation was employed. In the present paper, the depths of interfaces and respective resistivities are given and a comparison has also been made from the results obtained by Moore's cumulative method of interpretation,